On the origin of the animal style in the Kazakh steppe - Novozhenov, V.A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The Scythian-Saka animal style, its bizarre, phantasmagoric images and their territorial distribution in synchronous monuments on the vast territory of the Eurasian continent are clear evidence of the developed transcontinental visual, and in fact, symbolic and figurative communications of the Early nomads during this period. The phenomenon of the origin of this style and its geographical distribution, the decoding of images and communicative messages obviously finds its origins in Kazakh figurative monuments, clearly demonstrating its continuity, originality and origins in the local pictorial traditions of the Bronze Age.
Қазақ даласындағы аң стилінің пайда болуы туралы
О происхождении звериного стиля в Казахской степи
Keywords: petroglyphs; statuary sculptures; Deer stones; horses in masks with horns; Shan Rong; wolfdragons; Betpakdala; Karasuk Pictorial Tradition; Begazy-Dandybaev Culture